2018
DOI: 10.1051/matecconf/201821203005
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and utilization of liquid communal waste in the cities

Abstract: Treatment and further utilization of wastewater sludge are the important city service problem. The paper presents an efficient method of super high frequency irradiation for communal liquid waste such as wastewater sludge. The effect of microwaves on the properties of sediments, including the outlet of heavy metal ions in to water, is shown. Technical and economic indexes and results of experimental researches, indicating the opportunities of microwave irradiation in processes of sediments heating, are present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…It is confirmed in the materials [25][26][27], which use the Netherlands, Kenya, China, and other countries as examples of MW-heating of faecal sludge (Figure 2). Under the influence of MW, several parameters such as strength, frequency, duration, treatment temperature, and sample volumes [9,14,[22][23][24][25][26][27] can influence the efficiency of pollutant decomposition and mineralisation of wastewater and sediments. It is confirmed in the materials [25][26][27], which use the Netherlands, Kenya, China, and other countries as examples of MW-heating of faecal sludge (Figure 2).…”
Section: Heating and Thermal Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…It is confirmed in the materials [25][26][27], which use the Netherlands, Kenya, China, and other countries as examples of MW-heating of faecal sludge (Figure 2). Under the influence of MW, several parameters such as strength, frequency, duration, treatment temperature, and sample volumes [9,14,[22][23][24][25][26][27] can influence the efficiency of pollutant decomposition and mineralisation of wastewater and sediments. It is confirmed in the materials [25][26][27], which use the Netherlands, Kenya, China, and other countries as examples of MW-heating of faecal sludge (Figure 2).…”
Section: Heating and Thermal Treatmentmentioning
confidence: 99%
“…It should be noted that the technological and economic efficiency of MW heating for the water environment is currently actively explored by contrasting it to other methods of heating and processing [14,23,24]. The Department of Water Supply and Sanitation (Industrial University of Tyumen, Russia) laboratory has carried out several experiments related to the MW-heating of wastewater sludge [14,24]. Firstly, a comparison is made between microwave and electric heating.…”
Section: Heating and Thermal Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Wastewater and liquid waste present an important service problem in municipalities. In this area, Vialkova et al [32] evaluated and confirmed an energy-efficient economy for microwave irradiation, using municipal wastewater sediments [32,33].…”
Section: Present State Of Problem Solvingmentioning
confidence: 99%
“…Wastewater also presents the city service problem. Vialková et al [46] found an effective method for the treatment with liquid waste. The research confirmed the energy-efficient economy of microwave irradiation using municipal wastewater sediments.…”
Section: Literature Reviewmentioning
confidence: 99%